RECONSTRUCTING ENTREPRENEURSHIP IN THE CREATIVE DIGITAL ERA: SOCIAL INNOVATION THROUGH IMMERSIVE TECHNOLOGIES - Jung Yuna; Lim Haeun; Laura Lehtonen; Nurul Ulya (Journal of Social Entrepreneurship and Creative Technology, 2026)
The rapid evolution of immersive technologies, such as Virtual Reality (VR) and Augmented Reality (AR), is reshaping the landscape of entrepreneurship, particularly within the context of social innovation. As digital technologies continue to disrupt traditional business models, entrepreneurs are leveraging these innovations to create socially impactful ventures that not only meet market demands but also address critical societal challenges. This study investigates how immersive technologies are integrated into entrepreneurial practices to foster social sustainability, with a particular focus on businesses aiming to create positive change within marginalized communities. The research employs a mixed-methods approach, including qualitative interviews with entrepreneurs and quantitative analysis of business outcomes. The findings demonstrate that entrepreneurs using VR and AR technologies report increased customer engagement, enhanced operational efficiency, and a measurable social impact, particularly in the fields of education, healthcare, and community development. The study concludes that integrating immersive technologies with human-centered values enables businesses to create sustainable models that balance economic success with social good. This research contributes to the growing field of social entrepreneurship by highlighting the potential of digital innovations to drive social change and offering practical insights into how entrepreneurs can use these technologies to address global challenges.